Ativação imune neonatal por lipopolissacarídeo associada ao estresse na adolescência: estudo de alterações comportamentais, neuroquímicas e da influência do sexo em ratos adultos - Viana, Thaisa Marjore Menezes (2016)
The two-hit model proposes that genetic or behavioral challenges in periods considered critical in neurodevelopment, as early in life and during the transition from childhood to adolescence, can affect the normal development of the brain and predispose the individual to psychopathology. These events can occur differently between genders. The objective of this study was to investigate the behavioral and neurochemical changes in rats adults, male and female, after exposure to neonatal lipopolysaccharide (LPS) and stress in adolescence. In the neonatal period, 5th postnatal day (PN) and 7th Wistar rats received intraperitoneal LPS at a dose of 50 µg/kg or saline (1 challenge model) and between the PN35-PN43 (peripuberal period) the animals were submitted or not to stress (2 challenges model). On PN60 (young adult) was performed behavioral tests (open field, forced swimming, sucrose test, social interaction, Y maze, pre-pulse inhibition) and neurochemical analyzes (myeloperoxidase activity and brain-derived neurotrophic factor levels). In the open field there was an increase in the number of rearing in the group LPS + stress of males (p <0.005). Regarding the spent time in the central area there was a significant reduction in the group Salina + stress (p <0.01) and group LPS + stress (p <0.0001) when compared to control females. In the forced swimming test was observed in all groups, both in males and in females, a decrease in the immobility time when compared to the control, but was not observed anhedonia in sucrose test. IPP showed a reduction in the startle reflex in prepulse intensity at 70 in the group LPS + without stress (p <0.05) males. There was a decline in cognitive deficits by Y maze test in LPS + stress group in males (p <0.001) and females (p <0.05) and in the group LPS + without stress in males and females (p < 0.05). In social interaction males showed a decrease in percentage of time in the chamber with the animal (p <0.0001), in the input chamber with the animal (p <0.05) and in the time interacting with the animal (p <0.001). There were no significant changes in myeloperoxidase activity and it has an increase in BDNF levels in the hippocampus of LPS + stress group both males (p <0.0001) and females (p <0.01). The exposure to neonatal of the LPS showed behavioral and neurochemical changes in rats adults (male and female) with characteristics of Autistic Spectrum Disorder.